Should drug discovery scientists still embrace the amyloid hypothesis for Alzheimer's disease or should they be looking elsewhere?. (1st November 2020) - Imbimbo, Bruno Pietro; Ippati, Stefania; Watling, Mark
ABSTRACT: Introduction: Alzheimer's Disease (AD) represents a large and growing challenge to patients, carers and healthcare systems, yet extensive efforts to develop therapeutics to modify its course have been met with repeated failure in recent decades. Although the evident presence of accumulated β-amyloid (Aβ) in AD brains has singled it out as an obvious therapeutic target, the effective reduction of plaque load or soluble Aβ by numerous drug candidates has not produced commensurate clinical benefits – calling into question the Aβ cascade hypothesis of AD. A similar path is now unfolding in the pursuit of therapeutics targeting hyperphosphorylated tau-comprised neurofibrillary tangles. Areas covered: This perspective reviews the basis of the Aβ cascade hypothesis of AD and how clinical trials of anti-Aβ drugs have failed to support it, and reflects upon the early findings suggesting that a similar path is being followed with therapeutics targeting tau. Other potential approaches to identifying therapeutics for AD are explored herein. Expert opinion: The relevance of the Aβ cascade hypothesis to the development of therapeutics for AD appears disproven. Drugs targeting tau appear to be suffering the same fate but may yet produce better results. Alternative approaches are being pursued, some of them with initial small-scale, but promising, results.